Finite-strain laminates: Bending-enhanced hexahedron and delamination - Areias, P.; Rabczuk, T.; Camanho, P.P. (Composite structures, 2016)
With a new finite strain anisotropic framework, we introduce a unified approach for constitutive modeling and delamination of composites. We describe a finite-strain semi-implicit integration algorithm and the application to assumed-strain hexahedra. In a laminate composite, the laminae are modeled by an anisotropic Kirchhoff/Saint-Venant material and the interfaces are modeled by the exponential cohesive law with intrinsic characteristic length and the criterion by Benzeggagh and Kenane for the equivalent fracture toughness. For the element formulation, a weighted least-squares algorithm is used to calculate the mixed strain. Löwdin frames are used to model orthotropic materials without the added task of performing a polar decomposition or empirical frames. To assess the validity of our proposals and inspect step and mesh size dependence, a least-squares based hexahedral element is implemented and tested in depth in both deformation and delamination examples.